A Systematic Literature Review of Six Sigma Implementation on the Automotive Component Industry - Parid, Yaman; Hardi Purba, Humiras; Santoso, Suprapto (TALENTA Publisher, 2023)
The main purpose of this white paper is to analyze current research on Six Sigma in the auto parts industry and identify opportunities for further research. This study used a systematic literature search of the most recent scientific articles (2013-2022) searched using specific inclusion and exclusion criteria. His two main categories of research goals emerged. The development of Six Sigma and the impact of Six Sigma. In recent years, research on the impact of Six Sigma is the most popular and has always been there from year to year, while research on the development of Six Sigma is the least popular. The study can provide insights to researchers, consultants and quality managers in developing and implementing Six Sigma in the automotive components industry sector. This research found that there is a lot of research on the complete Six Sigma methodology in the automotive component industry, especially research on the impact of implementing Six Sigma. From these findings, the main avenue for future research can be identified, namely Six Sigma Digitalization.